2022
DOI: 10.3390/diagnostics12030758
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Pancreatic Hamartoma Associated with Hepatoblastoma—An Unusual Tumor Association

Abstract: Abdominal tumor masses are a very rare disease in the fetus. The authors present the first reported case of neonatal multicystic adenomatoid hamartoma of the pancreas associated with well-differentiated fetal epithelial subtype hepatoblastoma and reveal clinical, histologic, and imagistic aspects. Case presentation: A 36-week-old female newborn in whom a 25-week ultrasound showed a relatively homogeneous pancreatic echogenic mass (34 × 30 × 55 mm) with compression of the inferior vena cava and retrograde dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Different studies showed illiteracy, poverty, and mother occupation as the risk factors significantly associated with VLBW in 2016 highlighting hypocalcemia and hypoglycemia as the risk factors of VLBW [26]. Hypoglycemia problem arises due to the decreased storage of glycogen and fat.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies showed illiteracy, poverty, and mother occupation as the risk factors significantly associated with VLBW in 2016 highlighting hypocalcemia and hypoglycemia as the risk factors of VLBW [26]. Hypoglycemia problem arises due to the decreased storage of glycogen and fat.…”
Section: Resultsmentioning
confidence: 99%
“…Our case shows that pancreatic hamartoma can be preoperatively diagnosed using EUS–FNAB. Pancreatic hamartoma is a very rare, non‐neoplastic, mass‐forming pancreatic lesion, 1 with only 64 cases reported in the English literature and 7 in the Japanese literature, without abstract only (based on literature searches using the PubMed and Japanese Ichushi databases) 1–51 . As pancreatic hamartoma is typically asymptomatic, in more than half the abovementioned reports, the cases has been incidentally discovered 1–51 .…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic hamartoma is a very rare, non‐neoplastic, mass‐forming pancreatic lesion, 1 with only 64 cases reported in the English literature and 7 in the Japanese literature, without abstract only (based on literature searches using the PubMed and Japanese Ichushi databases) 1–51 . As pancreatic hamartoma is typically asymptomatic, in more than half the abovementioned reports, the cases has been incidentally discovered 1–51 . Furthermore, preoperative diagnosis using various techniques, such as CT, MRI, or US, is extremely difficult because various neoplasms, such as NET, solid pseudopapillary neoplasm, and adenocarcinoma, are included in the differential diagnosis, as described in the case report and literature review by Noguchi et al 1 In our case, the imaging findings suggested NET, although some features were atypical.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors for hepatoblastoma include the tumor's PRETEXT stage, Evans stage, AFP level at diagnosis, and pathological classification. They are also associated with early detection and timely chemotherapy and surgical treatment before distant metastasis, occurrence of respiratory and heart failure and tumor rupture due to compression effects (14)(15)(16). To improve the prognosis of infants with hepatoblastoma, the importance of early treatment should be emphasized.…”
Section: -Weeks' Gestationmentioning
confidence: 99%